2013
DOI: 10.1093/toxsci/kft116
|View full text |Cite
|
Sign up to set email alerts
|

Paraquat-Induced Ultrastructural Changes and DNA Damage in the Nervous System Is Mediated via Oxidative-Stress-Induced Cytotoxicity in Drosophila melanogaster

Abstract: Paraquat (PQ), a quaternary nitrogen herbicide, is commonly used as a pesticide despite of its high toxicity. Our study evaluated the effect of subchronic PQ exposure on the neuropathology, genotoxicity, and antioxidant activity on the nervous tissue of Drosophila melanogaster. We also explored the behavioral effect of PQ on D. melanogaster. Furthermore, we attempted to validate the mechanism by evaluating PQ-induced cytotoxicity on the D-Mel2 cell lines. The fruit fly D. melanogaster serves as a feasible mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 25 publications
2
20
0
1
Order By: Relevance
“…To extend our findings, we turned to the model organism Drosophila melanogaster, which is sensitive to inducers of oxidative stress. 34 Drosophila expresses one RNASET2 homolog, RNase X25, which is induced by ROS and promotes cell death when overexpressed. 28,35 Constitutive, whole body knockdown of RNase X25 did not result in viable progeny, underscoring the importance of RNase X25 in general housekeeping functions.…”
Section: Resultsmentioning
confidence: 99%
“…To extend our findings, we turned to the model organism Drosophila melanogaster, which is sensitive to inducers of oxidative stress. 34 Drosophila expresses one RNASET2 homolog, RNase X25, which is induced by ROS and promotes cell death when overexpressed. 28,35 Constitutive, whole body knockdown of RNase X25 did not result in viable progeny, underscoring the importance of RNase X25 in general housekeeping functions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, PQ-induced ROS production causes DNA damage: single-and double-strand DNA breaks, base modifications, deoxyribose fragmentation, DNA -protein cross-links, and abasic sites [10,11]. Recently, a significant increase in comet tail-length in PQ-treated Drosophlia melanogaster and decreased superoxide dismutase activity have been reported, suggesting a correlation of oxidative stress and DNA damage in vivo [12]. The comet (single-cell gel electrophoresis) assay is widely used in genotoxicity testing to evaluate DNA-damage.…”
Section: Introductionmentioning
confidence: 99%
“…Overall neurodegeneration in the substantia nigra (Manning-Bog et al, 2003;McCormack et al, 2005;Purisai et al, 2007), striatum (Rappold et al, 2011), locus coeruleus (Fernagut et al, 2007) and in brains of fruit flies (Mehdi & Qamar, 2013) has also been reported. Lastly, locomotor deficits have been observed in paraquat-exposed rodents (Choi et al, 2010b;Fredriksson et al, 1993;Liou et al, 1996) and fruit flies (Mehdi & Qamar, 2013).…”
Section: Supporting Publications 2016: En-955 74mentioning
confidence: 93%
“…The most-studied key downstream events of paraquat-induced neurotoxicity are apoptotic cell death observed from cell lines (Garcia-Garcia et al, 2013;Gonzalez-Polo et al, 2009;Gonzalez-Polo et al, 2007;Klintworth et al, 2007;McCarthy et al, 2004;Mehdi & Qamar, 2013;Peng et al, 2005;Ramachandiran et al, 2007;Rappold et al, 2011;Richardson et al, 2005;Wu et al, 2005;Yang & Tiffany-Castiglioni, 2005) and dopaminergic neurodegeneration observed from primary neurons (Choi et al, 2010b;Klintworth et al, 2007;Peng et al, 2005;Wu et al, 2005). The activation of MAP kinases JNK in neurons and ERK1/2 in microglia has been demonstrated to be an upstream event of paraquat-induced apoptosis (Choi et al, 2010b;Klintworth et al, 2007;Peng et al, 2005;Ramachandiran et al, 2007).…”
Section: Paraquatmentioning
confidence: 99%
See 1 more Smart Citation